Scaling up availability, accessibility, quality and equity – highlights from the 4th Uganda conference on cancer and palliative care, held in Kampala, Uganda - Downing, Julia; Mwebesa, Eddie; Asasira, Judith; Basemera, Bernadette; Adong, Dorothy Olet; Mwesiga, Mark (ecancermedicalscience, 2023)
The 4th Uganda Conference on Cancer and Palliative Care was held from the 14th–15th September 2023. It was run jointly by the Uganda Cancer Institute and the Palliative Care Association of Uganda, in collaboration with the Ministry of Health. The conference was held at the Speke Resort, Munyonyo and 450 participants came together for a face-to-face conference following the virtual one held in 2021. It was an opportunity for all those working in the fields of cancer and palliative care to come together, to share lessons and learn from each other, as well as celebrate 30 years since specialist palliative care came to Uganda. The conference was officially opened by the Commissioner for Non-Communicable Diseases on behalf of the Minister of Health, who reiterated the Government’s commitment to reducing the burden of cancer and expanding the provision of palliative care within Uganda. Dr Tedros Adhanom Ghebresus, the Director General of the World Health Organization welcomed participants to the conference, and the Assistant Bishop of Kampala Diocese, the Right Reverend Hannington Mutebi shared his experience of living with cancer. The conference was organised into six tracks: Innovations and new technologies; Education, advocacy, policy and law; Health promotion, prevention and early detection; Family and community involvement and empowerment; Clinical care and symptom management; and, Psychological, social and spiritual care. The themes of paediatrics, vulnerable populations, service development and research were integrated throughout the tracks, and workshops were held that explored topics such as governance, access to essential medicines, national data reporting, research and education, and aging and ageism. Throughout the conference there was a sense of optimism, of resilience and a commitment to the ongoing development of cancer and palliative care services within the country.